Dielectric and spectroscopic properties of copolymers based on methacrylate carrying coumarin side group - Akman, Feride; Demirelli, Kadir (Taylor & Francis Ltd, 2016)
A methacrylic monomer 7-methacryloyloxy-4-methylcoumarin (MAOMC) was synthesized by reacting 7-hydroxy-4-methyl coumarin with methacryloyl chloride. Copolymerization of MAOMC with styrene (St), ethyl methacrylate (EMA), methyl methacrylate (MMA), n-butyl methacrylate (nBMA) and isobutyl methacrylate (IBMA) were performed by the free radical polymerization method (FRP) at low conversions. The resulting polymers were characterized by H-1 NMR, FTIR, fluorescence and UV-vis spectroscopy. Dielectric properties of copolymers were measured by means of an impedance analyzer as a function of frequency and temperature. Dielectric measurements of copolymers prepared in a plate form were performed at room temperature over the frequency range 0.1 kHz-2 MHz and given as compared with each other. It was found that the dielectric constant of copolymers diminished in the applied frequency range. The optimized structural geometry and HOMO and LUMO energies of copolymers were carried out by density functional theory (DFT/B3LYP) method with 3-21G* as a basis set.
Keywords: 7-Methacryloyloxy-4-methylcoumarin; dielectric properties; DFT; HOMO-LUMO; fluorescence